Enhancement of functional characteristics of blueberry juice fermented by Lactobacillus plantarum. (March 2021) - Zhang, Yu; Liu, Weipeng; Wei, Zehua; Yin, Boxing; Man, Chaoxin; Jiang, Yujun
Abstract: Lactic acid bacteria with various probiotic functions and excellent fermentation characteristics are widely used in food production, which not only enhance flavor, but also improve functional quality. In this research, Lactobacillus plantarum J26 was selected as the fermented strain in blueberry juice, and the basic indexes, nutritional functional properties, antioxidant capacity and enzyme inhibition were tested to judge the fermentation process influences to blueberry matrix. The results showed that the total amount of phenolic substances increased by 43.42% after fermentation. Four kinds of anthocyanins were found through High Performance Liquid Chromatography (HPLC) detection. Then the scavenging abilities of DPPH, superoxide anion radical and hydroxyl radical were estimated to determine the antioxidant activities of fermented blueberry juice. Moreover, the effect of oxidative damage was also analyzed in the model of Caco-2 cells. Finally, the inhibition of α-glucosidase and α-amylase were both detected in fermented blueberry juice. To sum up, these findings suggested that L. plantarum J26 could be used as fermented strain in the blueberry juice to improve the functional activities. Highlights: The amount of phenols in fermented blueberry juice was increased significantly. Four kinds of anthocyanins were found in fermented blueberry juice. The antioxidant activity was enhanced significantly after fermented by L. plantarum J26. The inhibition of α-glucosidase and α-amylase were both improved after fermentation.